P2.44 No differences in knowledge of key hiv test concepts between users of an online sti testing service (getcheckedonline.com) and in-clinic testers in vancouver, canada. (8th July 2017) - Salway, Travis; Thomson, Kimberly; Taylor, Darlene; Elliot, Elizabeth; Wong, Tom; Fairley, Christopher; Haag, Devon; Grennan, Troy; Shoveller, Jean; Ogilvie, Gina; Gilbert, Mark
Abstract : Introduction: Online HIV/STI testing is an alternative to in-clinic testing, but may lead to missed opportunities for education due to the lack of provider-delivered pre/post-test counselling. GetCheckedOnline (GCO) is an online testing service offered through an urban STI clinic in Vancouver. It was designed to include concepts typically conveyed during in-clinic HIV counselling sessions (e.g., window period, public health reporting). The aim of this study was to compare knowledge of key HIV test concepts between clients testing through GCO and in-clinic. Methods: GCO and clinic participants were concurrently recruited over 11 months. Participants were invited to complete an anonymous online survey 2 weeks after receipt of test results. Knowledge of key concepts related to HIV testing was measured using a 6-item true/false test previously developed through a modified Delphi process, cognitive testing and psychometric evaluation. Linear regression was used to assess the association between site (GCO vs. clinic) and overall test scores, after adjustment for age, education, immigration history, language, sexual orientation, and testing history. Results: 404 HIV-negative participants were included in the analysis (73 GCO, 331 in-clinic). HIV test knowledge scores averaged 0.4 points higher among GCO (mean score 4.5) than among clinic (4.1) testers (p=0.01). Following adjustment for relevant covariates, this difference decreased to 0.2 points (p=0.15). Likewise, there was no difference in mean HIV test knowledge scores among first-time testers (n=50; 3.7 GCO, 3.6 in-clinic; p = 0.75). Conclusion: Post-test knowledge of HIV test concepts addressed in standard pre-test counselling was high in both groups and not significantly different following adjustment. Our study suggests that equivalent education about core HIV testing concepts can be achieved through web-based HIV/STI testing, and illustrates the importance of designing services to intentionally address relevant educational messages covered in provider-delivered HIV test counselling.